2015
DOI: 10.1589/jpts.27.117
|View full text |Cite
|
Sign up to set email alerts
|

The effects of shoulder joint abduction angles on the muscle activity of the serratus anterior muscle and the upper trapezius muscle while vibrations are applied

Abstract: [Purpose] The purpose of this study was to examine the ratio between the upper trapezius and the serratus anterior muscles during diverse shoulder abduction exercises applied with vibrations in order to determine the appropriate exercise methods for recovery of scapular muscle balance. [Subjects and Methods] Twenty-four subjects voluntarily participated in this study. The subjects performed shoulder abduction at various shoulder joint abduction angles (90°, 120°, 150°, 180°) with oscillation movements. [Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Previous studies have shown that shoulder joint positions could affect muscle activation 25 , 26 , 27 ) around the shoulder and the shoulder’s rotational strength 14 , 15 , 18 ) . The present study also found that the ER and IR strengths of the shoulder changed with the shoulder abduction angles in the scapular plane.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that shoulder joint positions could affect muscle activation 25 , 26 , 27 ) around the shoulder and the shoulder’s rotational strength 14 , 15 , 18 ) . The present study also found that the ER and IR strengths of the shoulder changed with the shoulder abduction angles in the scapular plane.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects were then instructed, with their arm raised in the same measured position, to resist a downward force of 5 pounds applied to the humerus with a hand-held dynamometer (Lafayette Instrument Co) by an experimenter, to achieve MVIC. (Figures 4, 5) Manual resistance at a shoulder abduction angle of about 120 degrees has been shown to achieve higher serratus anterior activation than other MVIC positions (Jung and Moon, 2015).…”
Section: [ Figure 3 ]mentioning
confidence: 91%
“…4 and 5 ). Manual resistance at a shoulder abduction angle of about 120° has been shown to achieve higher serratus anterior activation than other MVIC positions ( Jung & Moon, 2015 ).…”
Section: Methodsmentioning
confidence: 99%